THE EFFECT OF THE MARMET TECHNIQUE ON BREAST MILK EXPRESSION IN POSTPARTUM MOTHERS: A STUDY AT PMB SYAFLINA FITRI - Fahmi, Yuyun Bewelli; Andriana; Nurkhasanah, Siti; Santika, Lia (INTERNATIONAL JOURNAL OF MIDWIFERY AND BEAUTY, 2025)
Postpartum is part of maternity midwifery, namely providing quality and professional health services, identifying and adapting to the needs of breast milk is the best food for babies, breast milk is beneficial for the growth and development of breast milk babies. The content of breast milk is rich in immune substances (immunoglobin) which can protect babies from various infections. This study aims to determine the smoothness of breast milk production before and after the marmet technique is performed on postpartum mothers from day one to day three at the Syaflina Fitri Midwife Practice. This research method is quantitative research using a design using a one-group design. In this design, there are pre-tests and post-tests before and after being carried out. The sampling technique in this study is the saturated sampling technique which is part of the population selected in a certain way so that it is considered capable of representing the population. The sample of this study was postpartum mothers at the Syaflina Fitri Pasir Pengaraian Midwife Practice as many as 15 respondents where the populations in this study were used as samples, namely 15 respondents. For data analysis using the T-Dependent statistical test, the p-value = 0.000 was obtained, thus, the p-value (0.000) <0.05, indicates that there is an effect of the Marmet technique on the smoothness of breast milk in postpartum mothers. It is expected to be useful and add information and input in efforts to improve information and the quality of health services and to motivate postpartum mothers to apply the Marmet technique for smooth breast milk.